2004
DOI: 10.1002/em.20052
|View full text |Cite
|
Sign up to set email alerts
|

Potential chemoprotective effects of the coffee components kahweol and cafestol palmitates via modification of hepatic N‐acetyltransferase and glutathione S‐transferase activities

Abstract: Coffee drinking has been associated with reduced incidence of colorectal cancer, possibly via chemoprotection/modification of the metabolism of dietary heterocyclic amine carcinogens such as 2-amino-1-methyl-6-phenylimidazo-[4,5-b]pyridine (PhIP) by kahweol and cafestol palmitates (K/C), two components of unfiltered coffee. Using the PhIP-exposed male Fisher F344 rat as a model, K/C have been shown to reduce colonic PhIP-DNA adducts by > 50%. We have used the male F344 rat to investigate the effects of dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 69 publications
(79 reference statements)
1
32
1
Order By: Relevance
“…Recently, coffee diterpenes were found to increase the GSH and c-GCS level in a hepatoma cell line in a dose-dependent manner [79] and hepatic GSH and GSH S-transferase (GST) activity in rats [80]. These data suggested that coffee diterpenes have chemoprotective effects through stimulation of the endogenous antioxidant system via a mechanism which presumably involves transcription factors, such as AP-1, Nrf2, and c-jun [81,82].…”
Section: Mechanisms Of Coffee Consumption Involved In Cardiovascular mentioning
confidence: 96%
“…Recently, coffee diterpenes were found to increase the GSH and c-GCS level in a hepatoma cell line in a dose-dependent manner [79] and hepatic GSH and GSH S-transferase (GST) activity in rats [80]. These data suggested that coffee diterpenes have chemoprotective effects through stimulation of the endogenous antioxidant system via a mechanism which presumably involves transcription factors, such as AP-1, Nrf2, and c-jun [81,82].…”
Section: Mechanisms Of Coffee Consumption Involved In Cardiovascular mentioning
confidence: 96%
“…However, it can also inhibit carcinogenesis in vivo and alter carcinogen metabolism, decreasing the cytotoxic, cytostatic, or mutagenic activity of aromatic DNA-damaging compounds through a decrease in the concentration of free aromatic procarcinogens available for cytochrome activation 4,5 . The protective effects of coffee were partially ascribed to the potential for kahweol and cafestol palmitates to convert rapid acetylators into a slow acetylator phenotype 6 . These diterpenes may also have anti-inflammatory and anti-carcinogenic properties by interfering with nitric oxide 7 , prostaglandin E2 production, and cyclooxigenase-2 expression 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that the possibly protective effect of coffee against CRC found in some studies may be related to antioxidant and antimutagenic effects of phenolic compounds (mainly chlorogenic acid), 6,33 inhibition of colon cancer cell growth by caffeine, 8,9 and cafestol and kahweol mediated reduction of bile acid synthesis 2,34,35 and inhibition of CYP1A2 and NAT2 activity. [36][37][38][39] In addition, caffeine may specifically protect against distal colon cancer by increasing the motility of the distal colon and, as a consequence, lowering carcinogen exposure of colonic epithelial cells. 7 Although in the present study specific data on caffeinated and decaffeinated coffee was only available in approximately half of the participating centers, separate analyses for caffeinated coffee did not demonstrate a significant protective effect of caffeinated coffee against CRC.…”
Section: Discussionmentioning
confidence: 99%